Sense and Sensibility - Austen, Jane, 1775-1817 (London Penguin Books, 1994)
When two sisters appear to be deserted by the young men they had intended to marry, the stage is set for a delicious comedy of manners that not only showcases Austen's perception, humor and incomparable prose, but offers a splendid glimpse of upper and middle-class English society of the early 19th century.
Keywords: England -- Young women -- Sisters -- Manners and customs